Whole-exome sequencing enables rapid and prenatal diagnosis of inherited skin disorders - Zhu Xintong; Zhang Kexin; Wang Junwen; Wang Ziyi; Luo Na; Guo Hong (BMC, 2023)
Abstract Background Genodermatoses are a broad group of disorders with specific or non-specific skin-based phenotypes, most of which are monogenic disorders. However, it's a great challenge to make a precise molecular diagnosis because of the clinical heterogeneity. The genetic and clinical heterogeneity brings great challenges for diagnosis in dermatology. The whole exome sequencing (WES) not only expedites the discovery of the genetic variations, but also contributes to genetic counselling and prenatal diagnosis. Materials and methods Followed by the initial clinical and pathological diagnosis, genetic variations were identified by WES. The pathogenicity of the copy number variations (CNVs) and single-nucleotide variants (SNVs) were evaluated according to ACMG guidelines. Candidate pathogenic SNVs were confirmed by Sanger sequencing in the proband and the family members. Results Totally 25 cases were recruited. Nine novel variations, including c.5546G > C and c.1457delC in NF1, c.6110G > T in COL7A1, c.2127delG in TSC1, c.1445 C > A and c.1265G > A in TYR, Xp22.31 deletion in STS, c.908 C > T in ATP2A2, c.1371insC in IKBKG, and nine known ones were identified in 16 cases (64%). Prenatal diagnosis was applied in 6 pregnant women by amniocentesis, two of whom carried positive findings. Conclusions Our findings highlighted the value of WES as a first-tier genetic test in determining the molecular diagnosis. We also discovered the distribution of genodermatoses in this district, which provided a novel clinical dataset for dermatologists.